2021
DOI: 10.1021/acsanm.1c01205
|View full text |Cite
|
Sign up to set email alerts
|

CoO Nanotubes Loaded on Graphene and Modified with Porphyrin Moieties for Colorimetric Sensing of Dopamine

Abstract: In this paper, CoO nanotubes loaded on the surface of graphene oxide (GO) have been first modified by 5,10,15,20tetrakis(4-carboxyl phenyl)porphyrin (Por) by a hydrothermal method. Por/CoO/GO exhibits excellent peroxidase-like activity, which is evaluated by virtue of the chromogenic substrate 3,3,5,5tetramethylbenzidine (TMB). In the presence of H 2 O 2 , Por/CoO/ GO nanoperoxidase can rapidly catalyze colorless TMB to be oxidized into blue oxTMB, which is distinguished visually in 1 min. The experimental dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Under strong acidic conditions, the amino groups of TMB get protonated and they are not able to donate their lone pair of electrons to the catalyst. [73,74] Thus, the catalytic activity of the catalyst is decreased. When pH > 5, number of OH À ions in the solution increases which leads to decomposition of H 2 O 2 .…”
Section: Effect Of Experimental Conditions On Peroxidase-like Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Under strong acidic conditions, the amino groups of TMB get protonated and they are not able to donate their lone pair of electrons to the catalyst. [73,74] Thus, the catalytic activity of the catalyst is decreased. When pH > 5, number of OH À ions in the solution increases which leads to decomposition of H 2 O 2 .…”
Section: Effect Of Experimental Conditions On Peroxidase-like Activitymentioning
confidence: 99%
“…When pH > 5, number of OH À ions in the solution increases which leads to decomposition of H 2 O 2 . [73] The generation of hydroxyl radicals decreases beyond pH = 5 and the catalytic activity is thus decreased. leaching on the peroxidase-like activity of Sn 1-x Fe x S 2 nanoparticles (SF-0.20).…”
Section: Effect Of Experimental Conditions On Peroxidase-like Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, in previous studies, CoO nanoparticles have often been doped with other substances as part of the catalyst. Few studies have used CoO nanoparticles alone as catalysts to participate in the reaction, and most of the related enzyme-like catalytic activities were peroxidase-like or oxidase-like [53][54][55][56]. In this paper, we prepared CoO nanoparticles with a "cluster" morphology, and the morphology of CoO nanoparticles can be changed by changing the reaction temperature.…”
Section: Relieve the Pathological Symptoms Of The Ear Skin Of Ad Micementioning
confidence: 99%
“…Co 3 O 4 nanozymes are widely used in cancer therapy, antiviral, magnetic resonance imaging (MRI), and targeted drug delivery [49][50][51]. At present, many studies have reported that CoO nanozymes with POD-like activity prepared by a variety of synthetic methods have extremely high application value in biosensing [52][53][54][55]; CoO nanostructures have the advantages of high stability, large specific surface area, and easy redox [56,57]. However, pure CoO nanoparticles show poor electrical conductivity and tend to self-aggregate to cover active sites.…”
Section: Introductionmentioning
confidence: 99%